PERSONAL DATA PROTECTION IN INDONESIA'S PEER-TO-PEER LENDING; A BIBLIOMETRIC ANALYSIS - Patra Anggaredho, Panji; Prihatni, Rida; Gurendrawati, Etty (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2025)
The rise of Peer-to-Peer (P2P) Lending in the financial ecosystem has introduced a digital credit disbursement mechanism characterized by simplicity and a fast process. However, P2P Lending has faced criticism, frequently accused of misusing customer data, particularly privacy violations during loan collection processes. Due to the ongoing issues with personal data protection in Indonesia’s P2P Lending industry, further studies on this topic are necessary. Moreover, previous studies have shown that no bibliometric analysis of personal data protection in P2P Lending in Indonesia has been conducted, which prompted us to address this gap. In conducting the bibliometric analysis, we reviewed articles published between 2018 and 2023 on Google Scholar. For the selection of articles, we used the Publish or Perish application, resulting in a final sample of 99 articles. This study concluded that the keyword "protection" is frequently associated with information, problem, benefit, trust, implementation, user, platform, and information security. Another finding shows that the subject of this study has increased since 2020 and remains highly relevant for further study. Furthermore, the subject of this study includes keywords that are rarely discussed, such as MSMEs (Micro, Small, and Medium Enterprises) and inclusion, indicating that future study could explore these two topics further.